Working Girls in the West: Representations of Wage-Earning Women - Jones, Esyllt W. (Labour / Le Travail, 2009)
The article reviews the book, "Working Girls in the West: Representations of Wage-Earning Women," by Lindsey McMaster.
Keywords: BOOKS -- Reviews; MCMASTER, Lindsey; Nonfiction; WAGES -- Women; WORKING Girls in the West: Representations of Wage-Earning Women (Book)